Effects of open and closed kinetics chain exercise on functional outcomes and lower limb biomechanics in mild primary knee osteoarthritis female patients - Hui, Ng Wei (2025)
Exercise is a key non-pharmacological intervention recommended for managing knee osteoarthritis (OA). Among the various modalities, open kinetic chain (OKC) and closed kinetic chain (CKC) exercises are commonly prescribed, yet their comparative effects on functional outcomes and lower limb biomechanics remain unclear. This study aimed to evaluate the impact of OKC and CKC interventions on pain, quality of life (QoL), muscle strength, functional performance, and biomechanics in individuals with primary mild knee OA. Sixty-six participants aged ≥50 years with early symptomatic OA and BMI between 18.9–29.9 kg/m² in Putrajaya, Malaysia were randomly assigned to OKC, CKC, or control groups. All underwent an initial physiotherapy session, followed by an eight-week home-based program. The exercise groups trained thrice weekly, while the control group received educational materials. Primary outcomes included pain (VAS), disability (WOMAC), and QoL (OAKHQOL); secondary outcomes assessed gait, sit-to-stand biomechanics, and isometric knee strength. Post-intervention analyses showed that both OKC and CKC exercises significantly improved pain, QoL, muscle strength, and functional performance. CKC yielded greater benefits in dynamic tasks, whereas OKC was better tolerated by those with higher pain sensitivity. These findings support incorporating tailored OKC and CKC exercises into physiotherapy to enhance mobility and QoL in knee OA patients.